2021
DOI: 10.3389/fphys.2021.729084
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes: Versatile Participants in Acute Kidney Injury and Progression to Chronic Kidney Disease

Abstract: Background: Acute kidney injury (AKI) remains a major global public health concern due to its high morbidity and mortality. The progression from AKI to chronic kidney disease (CKD) makes it a scientific problem to be solved. However, it is with lack of effective treatments.Summary: Both innate and adaptive immune systems participate in the inflammatory process during AKI, and excessive or dysregulated immune responses play a pathogenic role in renal fibrosis, which is an important hallmark of CKD. Studies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 138 publications
0
10
0
Order By: Relevance
“…Acute kidney injury is usually characterized by rapid decline in renal function, which results in acute kidney failure and other organ failure in severe cases. Acute kidney injury can be caused by a variety of factors, which include drug use, ischemia/reperfusion, and infection [ 15 17 ]. In recent years, the incidence and mortality of acute kidney injury have been increasing, and the mortality rate of severe acute kidney injury can reach more than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injury is usually characterized by rapid decline in renal function, which results in acute kidney failure and other organ failure in severe cases. Acute kidney injury can be caused by a variety of factors, which include drug use, ischemia/reperfusion, and infection [ 15 17 ]. In recent years, the incidence and mortality of acute kidney injury have been increasing, and the mortality rate of severe acute kidney injury can reach more than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the whole blood lymphocyte count is considered an indicator of the immune response in patients ( 34 ). In addition, lymphocytes, especially T cells, play a vital role in the whole evolution of kidney injury ( 35 ). In this study, we found that a higher whole blood lymphocyte count can increase the risk of post-LT AKI, rather than a low whole blood lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…Second, lymphocytes are components of adaptive immunity while T cells are emerging mediators involved in the development and recovery of AKI (38,42,43). Further studies are required to determine the speci c roles of platelets and lymphocytes in AKI.…”
Section: Discussionmentioning
confidence: 99%